2004
DOI: 10.1093/aob/mch214
|View full text |Cite
|
Sign up to set email alerts
|

Phytolith Assemblages in Grasses Native to Central Argentina

Abstract: This study highlights the possibility of reconstructing past vegetation in central Argentina grasslands through the analysis of soil phytolith assemblages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 22 publications
2
51
0
4
Order By: Relevance
“…Silica deposited as inclusions within the cells are usually termed as phytoliths or silica bodies. Phytoliths have proved to be a potential tool in palaeoecological studies as they remain stable in the soil for even millions of years after plant tissues decay [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Silica deposited as inclusions within the cells are usually termed as phytoliths or silica bodies. Phytoliths have proved to be a potential tool in palaeoecological studies as they remain stable in the soil for even millions of years after plant tissues decay [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Phytoliths, also called plant opals or opaline silica, are solid deposits of amorphous silica (SiO 2 .nH 2 O) that are produced in living plants and precipitated in and among their cells in organs such as stems, leaves and inflorescences (Metcalfe, 1960;Runge, 1999;Pearsall, 2000). In plant tissues phytoliths are deposited as discrete bodies in intracellular (cells and cell walls) and/or intercellular spaces (Piperno, 1988;Gallego and Distel, 2004). Many phytoliths are morphologically distinctive, although some taxa have less distinctive morphologies that are difficult to characterise by shape and size.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of silica occurs in various taxa (Hodson et al, 2005) and phytoliths are particularly abundant in the family Poaceae (Gramineae) (Rovner, 1971;Twiss, 1987;Gallego and Distel, 2004). After the plant dies, its organic matter is decomposed and the silica bodies, which are chemically stable, are resistant to decomposition and thus remain as microfossils in soils (Rovner, 1971;Twiss, 1987;Piperno, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Brown, 1984;Mulholland, 1989;Fredlund and Tieszen, 1994) and South American grasses (e.g. Gallego and Distel, 2004;Fernandez Honaine et al, 2006;Piperno and Pearsall, 1998), as well as the seminal works of Metcalfe (1960) and Watson and Dallwitz (1994 onwards) have generally confirmed the Twiss classification, but also demonstrated that numerous genera have deviating patterns of short cell phytoliths. However, the indices approach does not refer to single phytoliths diagnostic for species or genera, but to phytolith assemblages (Fredlund and Tieszen, 1994).…”
Section: Indices Vs General Approachmentioning
confidence: 86%